THU0021 DNA Methylation of Peripheral Blood Cell Subpopulations in Patients with Early Rheumatoid Arthritis before and after Methotrexate Treatment. (23rd January 2014) - de Andrés, M. C.; Perez-Pampin, E.; Calaza, M.; Ortea, I.; Gomez-Reino, J. J.; Gonzalez, A.
Abstract : Background: Epigenetic regulation influences gene expression and can affect disease course and treatment response. Global DNA methylation of T cells from patients with RA is decreased 1 . This hypomethylation could favour inflammation and tissue destruction through aberrant gene expression. However, little is known about this process and whether other blood cells are at play. Methotrexate (MTX) is widely used for the treatment of RA but its mechanism of action is not completely understood. It could include increased DNA methylation as already suggested in unseparated blood cells 2 . Objectives: To evaluate global DNA methylation and expression of enzymes involved in DNA methylation (DNMTs) and demethylation (GADD45a) in five peripheral blood cell subpopulations from patients with early RA before and after MTX treatment. Methods: T and B lymphocytes, monocytes, NK cells and granulocytes were separated by magnetic isolation from blood of 20 patients with early RA (baseline and after 4-6 weeks of MTX treatment) and 17 healthy controls (matched for gender and age). Genomic DNA and RNA were simultaneously extracted. Global methylation levels were assessed by HPLC-ESI-MRM and gene expression of DNMT1, DNMT3A, DNMT3B and GADD45A was determined by real time PCR. Results: Global DNA methylation of T cells in RA patients was significantly lower than in healthy controls (3.97 % ± 0.35 versus 4.23 % ± 0.45, P = 0.023). This difference was associated with about half DNMT1 expression in patients than in controls ( P = 0.014). DNMT1 expression was also lower in monocytes ( P = 0.0005) and B cells ( P = 0.013) from RA patients, although global DNA methylation was not significantly different. After 4-6 weeks of MTX treatment, DNA methylation in T cells of RA patients was increased to levels comparable with controls (4.23 % ± 0.43, P = 0.007 compared with baseline). DNA methylation also increased in monocytes ( P = 0.023). DNMT1 expression levels were also increased in T cells after MTX treatment ( P = 0.027). Conclusions: Compared with healthy controls, T cells of early RA patients show less DNA methylation associated with lower expression of the main methylation maintenance enzyme DNMT1 . These changes regress after MTX treatment. Similar but less prominent changes are observed in B cells and monocytes. These differences in peripheral blood cells could reflect important mechanisms both in disease evolution and its control by MTX. References: Richardson B et al. Arthritis Rheum. 1990;33:1665-73 Kim YI et al. J Lab Clin Med. 1996;128:165-72 Acknowledgements: Funding was provided by grant PI11/01048 and PI12/01909 of the Instituto de Salud Carlos III (Spain) that are partially financed by the European Regional Development Fund of the European Union. Disclosure of Interest: None Declared